1996
DOI: 10.1200/jco.1996.14.4.1282
|View full text |Cite
|
Sign up to set email alerts
|

Is radiotherapy curative for stage I and II low-grade follicular lymphoma? Results of a long-term follow-up study of patients treated at Stanford University.

Abstract: Radiotherapy remains the treatment of choice for early-stage low-grade follicular lymphomas. Patients who have remained free of disease for 10 years are unlikely to relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
181
2
18

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(217 citation statements)
references
References 17 publications
16
181
2
18
Order By: Relevance
“…Recurrences were more frequently observed in patients treated with EFI; however, there were imbalances of stage distribution and total irradiation dose and no multivariate analysis was performed. Mac Manus et al described the Stanford experience of 177 patients and differentiated between irradiation of the involved side or both sides of the diaphragm [4]. After a median follow-up of 7.7 years, FFP at 10 year were 36% and 67% for treatment of the involved side only and both sides of the diaphragm, respectively, which was highly significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrences were more frequently observed in patients treated with EFI; however, there were imbalances of stage distribution and total irradiation dose and no multivariate analysis was performed. Mac Manus et al described the Stanford experience of 177 patients and differentiated between irradiation of the involved side or both sides of the diaphragm [4]. After a median follow-up of 7.7 years, FFP at 10 year were 36% and 67% for treatment of the involved side only and both sides of the diaphragm, respectively, which was highly significant.…”
Section: Discussionmentioning
confidence: 99%
“…As the site of treatment failure is most frequently nodal outside irradiated involved volumes, extended-field irradiation (EFI) or even total nodal irradiation (TNI) have been proposed to improve outcome compared to involved-field irradiation (IFI). While studies reported improved progression free survival (PFS) after treatment of larger volumes, this did not transfer into improved overall survival (OS) [4,5]. Despite the majority of relapses are observed within 5 years after radiotherapy, late recurrences 15 – 20 years after treatment [4-6] indicate the need for studies with long-term follow-up, which are scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of a minority of patients who present with localized disease in which radiation therapy alone may have a curative role [2][3][4][5], it is considered a largely incurable disease. Disease progression is characterized by multiple relapses with spontaneous remission and transformation to more aggressive lymphomas in some cases.…”
mentioning
confidence: 99%
“…Together, these 'indolent' diseases are characterized by a relatively long-median survival; 8-10 years in the case of FL (Gallagher et al, 1986;Horning, 1993) and the clinical course is typically one of multiple disease episodes, punctuated by variable periods of remission. The tumours are sensitive to external beam radiotherapy, as demonstrated by the long-periods of relapse-free survival observed in patients with early stage disease treated with this modality (Mac Manus and Hoppe, 1996). For the majority of patients however, who have advanced stage disease, an initial policy of observational management is not disadvantageous in the absence of symptoms or organ compromise (Ardeshna et al, 2003).…”
Section: Introductionmentioning
confidence: 99%